ANALISIS BATAS USIA PERKAWINAN PADA UU NO. 16 TAHUN 2019 ATAS PERUBAHAN UU NO. 1 TAHUN 1974 TENTANG PERKAWINAN DALAM PERSPEKTIF MAQĀSHID ASY-SYARÎ’AH - Hasbullah, Hasbullah (Program Studi Hukum Keluarga Islam STAI Al-Falah Banjarbaru, 2024)
Abstract This study analyzes the amendment of the marriage age limit in Law No. 16 of 2019 as a revision of Law No. 1 of 1974 concerning Marriage, focusing on the perspective of Maqāshid Asy-Syarî’ah. The change in the marriage age aims to provide legal and social protection for children, especially girls, and to support family welfare. The research addresses the following issues: first, a comparison between the provisions of the marriage age limit in Law No. 16 of 2019 and Law No. 1 of 1974; second, the social and legal impacts of the amendment; and third, the perspective of Maqāshid Asy-Syarî’ah on the determination of the marriage age as regulated in the new law. Through normative analysis and a maqāshid-based approach, the study concludes that the amendment aims to protect human rights, prevent child exploitation, and ensure family welfare in line with the principles of Maqāshid Asy-Syarî’ah, particularly in the aspects of hifz al-nafs (protection of life) and hifz al-nasl (protection of offspring). Keywords: Marriage Age Limit, Law No. 16 of 2019, Maqāshid Asy-Syarî’ah, Social Impact, Legal Impact